2018
DOI: 10.1016/j.chb.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of reading skills in the evaluation of online information gathered from search engine environments

Abstract: Dieses Dokument steht unter folgender Creative Commons-Lizenz: http://creativecommons.org/licenses/by-nc-nd/4.0/deed.de -Sie dürfen das Werk bzw. den Inhalt unter folgenden Bedingungen vervielfältigen, verbreiten und öffentlich zugänglich machen: Sie müssen den Namen des Autors/Rechteinhabers in der von ihm festgelegten Weise nennen. Dieses Werk bzw. dieser Inhalt darf nicht für kommerzielle Zwecke verwendet werden und es darf nicht bearbeitet, abgewandelt oder in anderer Weise verändert werden.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 52 publications
(70 reference statements)
2
26
0
4
Order By: Relevance
“…It is worth noting that in the study by Salmerón et al (2018), more emphasis was placed on the navigational component of online reading than in the present study. On the other hand, Hahnel, Goldhammer, Kröhne, and Naumann (2018) found that lower level reading skills, namely performance in a sentence verification task, made a unique contribution in addition to reading comprehension when students evaluated search engine web page results. As such, our results suggest that lower level reading skills in early adolescence can contribute to ORC performance.…”
Section: Struggling Readers Face Difficulties In Online Research and mentioning
confidence: 99%
“…It is worth noting that in the study by Salmerón et al (2018), more emphasis was placed on the navigational component of online reading than in the present study. On the other hand, Hahnel, Goldhammer, Kröhne, and Naumann (2018) found that lower level reading skills, namely performance in a sentence verification task, made a unique contribution in addition to reading comprehension when students evaluated search engine web page results. As such, our results suggest that lower level reading skills in early adolescence can contribute to ORC performance.…”
Section: Struggling Readers Face Difficulties In Online Research and mentioning
confidence: 99%
“…It seems justifiable to conclude that time spent on digital reading can be a mixed blessing. Skilled navigation and source evaluation necessarily require good comprehension skills (e.g., Naumann, ) but the evidence suggests an asymmetry in that competent reading of linear printed text is a strong facilitator of competent digital reading but not vice versa (Hahnel, Goldhammer, Kröhne, & Naumann, ; Hahnel, Goldhammer, Naumann, & Kröhne, ; Naumann & Salmerón, ). It is plausible that intensive reading of superficial digital material instead of print reading is likely associated with comprehension problems and may even augment them.…”
Section: What Underlies the Correlation Between Reading Skills And Lementioning
confidence: 99%
“…In the research by Hahnel et al [26], both traditional and sustainable search engines were studied to find the factors which influence users' choice of search engines. Liaw and Huang [27] suggested a model to investigate the methods used to find information with search engines and identify how these searches can be made more efficient.…”
Section: Theoretical Backgroundmentioning
confidence: 99%